Validating the Constructivist Instructional Practices Scale for Cambodian High School Teachers Context: Exploratory and Confirmatory Factor Analysis - Sam OL Nguon; Hart Bunhe; Meak Chantheng (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aimed to develop and validate the constructivist instructional practices scale, grounded in constructivist learning theory, concentrated on three dimensions: teacher’s autonomy support, teacher’s support and feedback, and cooperative learning support. Methodology: 626 participants from 9 high schools across 4 provinces in Cambodia were selected conveniently. The data was analyzed by using an exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Main Findings: The initial 18-item instrument was refined to a 15-item scale after removing three items with weak, cross, or negative loadings. The final model confirmed a three-factor structure: Teacher Autonomy Support (TAS), Teacher Support and Feedback (TSF), and Cooperative Learning (CL).  The instrument demonstrated high internal consistency (Cronbach’s alpha > 0.80) and robust factorial validity (CFI > 0.95, RMSEA < 0.06), proving to be a reliable tool for measuring student-centered teaching behaviors. Novelty/Originality of this study: This research fills a critical gap by providing the first psychometrically validated scale for constructivist practices tailored to the Cambodian high school context.  It contributes to educational assessment by offering a reliable framework for evaluating the shift toward student-centered pedagogy in Southeast Asian classrooms.